Perbandingan Kinerja Toyota Kijang Model Innova G Produksi Tahun 2005 dan 2007 dengan Sistem Electrical Fuel Injection (EFI) - Joni; Pither Palamba (G-Tech: Jurnal Teknologi Terapan, 2023)
The increasing use of four-wheeled vehicles in land transportation now provides comfort in mobilization. The side effect of increasing exhaust emissions produced by vehicles is also increasing. Each make and model of four-wheeled vehicle has its own characteristics. One example is the Innova EFI, a model manufactured by Toyota and using an electronic fuel injection system. This car can reduce fuel consumption and reduce the impact of pollution at the combustion stage. The aim of this research is to determine the relationship between motor load variations and the composition of the exhaust gas produced. The measurements involve the use of a gas analyzer and a torque meter. The results showed that thermal efficiency reached its peak at 4000 rpm, for the 2005 Innova model the efficiency reached 29.49%, and the 2007 Innova reached 28.93%. The 2007 Toyota Innova vehicle has the lowest emission levels, with CO levels of 1.38% and HC 136 ppm.